2016
DOI: 10.4238/gmr.15028633
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and antitumor activity and diversity of endophytic fungi from traditional Chinese medicinal plant Cephalotaxus hainanensis Li

Abstract: ABSTRACT. Endophytes from Cephalotaxus hainanensisLi, an important source of anti-leukemia drugs, have not been widely explored. In this study, 265 endophytic fungal isolates from C. hainanensis Li were screened for antimicrobial activities against tilapia, banana, rice, and rape and for antitumor activities against human leukemia cell lines (K562, NB4, and HL-60). Diversity was also analyzed. The results showed that 17.7% of the endophytic fungi had antimicrobial activities against at least three different te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…106 Bioassays employing the clinical isolates of the human pathogens Enterococcus faecalis, Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa, and Klebsiella pneumoniae and plant fungal pathogens revealed that the majority of these Saudi endophytes isolated exerted moderate to high levels of antimicrobial activity against a wide assortment of human pathogens, iv) elucidation of endophytic symbionts of Cephalotaxus hainanensis Li, a chinese evergreen associated with anti-leukemia drugs from which 265 endophytic fungal isolates were identified, refined, and evaluated for antimicrobial [ Escherichia coli, Staphylococcus aureus, Bacillus subtilis, Streptococcus agalactiae (a pathogenic bacterium in Tilapia mossambic ) , Fusarium oxysporum, Rhizoctonia solani, and Sclerotinia sclerotiorum ] and anticancer activities. 107 Remarkably, 91 endophytic strains showed varying degrees of antimicrobial activity and 17.7% of these exerted activity against at least three different test microbes. The 30 most active strains reflect the importance of strains belonging to the Colletotrichum , Diaporthe , Phomopsis and Penicillium classifications of C. hainanensis Li symbionts, v) studies of Myrothecium fungal endophytes found in Calophyllum apetalum and Garcinia morella , medicinal plants are common to Western Ghats, Karnataka, India; evaluation of the antimicrobial activity and genetic variability of these endophytic isolates revealed that the various isolates can be grouped into four main clades and subgroups and that differences between endophytic (symbiotic) and pathogenic strains of Myrothecium could be readily differentiated on the basis of genetic analyses and data handling approaches.…”
Section: Plant-microbe Symbiosesmentioning
confidence: 99%
“…106 Bioassays employing the clinical isolates of the human pathogens Enterococcus faecalis, Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa, and Klebsiella pneumoniae and plant fungal pathogens revealed that the majority of these Saudi endophytes isolated exerted moderate to high levels of antimicrobial activity against a wide assortment of human pathogens, iv) elucidation of endophytic symbionts of Cephalotaxus hainanensis Li, a chinese evergreen associated with anti-leukemia drugs from which 265 endophytic fungal isolates were identified, refined, and evaluated for antimicrobial [ Escherichia coli, Staphylococcus aureus, Bacillus subtilis, Streptococcus agalactiae (a pathogenic bacterium in Tilapia mossambic ) , Fusarium oxysporum, Rhizoctonia solani, and Sclerotinia sclerotiorum ] and anticancer activities. 107 Remarkably, 91 endophytic strains showed varying degrees of antimicrobial activity and 17.7% of these exerted activity against at least three different test microbes. The 30 most active strains reflect the importance of strains belonging to the Colletotrichum , Diaporthe , Phomopsis and Penicillium classifications of C. hainanensis Li symbionts, v) studies of Myrothecium fungal endophytes found in Calophyllum apetalum and Garcinia morella , medicinal plants are common to Western Ghats, Karnataka, India; evaluation of the antimicrobial activity and genetic variability of these endophytic isolates revealed that the various isolates can be grouped into four main clades and subgroups and that differences between endophytic (symbiotic) and pathogenic strains of Myrothecium could be readily differentiated on the basis of genetic analyses and data handling approaches.…”
Section: Plant-microbe Symbiosesmentioning
confidence: 99%
“…Cephalotaxus hainanensis, an evergreen medicinal plant in the family Cephalotaxaceae, is distributed in the narrow range of the western Guangdong, Hainan, southeastern and western Guanxi, western Yunnan, and even southeastern Tibet, China (Yang and Liao 2013;Qiao et al 2014). This plant is suggested to have antileukemia, antidiabetic, anticancer and antitumor activities and is widely used as a herbal remedy in China (Pan et al 2010;Liu et al 2016). However, due to logging and more recently exploitation of bark and leaves which contain the valuable medicinal extracts, cephalotaxine and harringtonine, the number of the wild C. hainanensis has decreased sharply (Qiao et al 2014).…”
Section: Cephalotaxus Hainanensis; Illumina Sequencing; Chloroplast Gmentioning
confidence: 99%
“… 2010 ; Liu et al. 2016 ). However, due to logging and more recently exploitation of bark and leaves which contain the valuable medicinal extracts, cephalotaxine and harringtonine, the number of the wild C. hainanensis has decreased sharply (Qiao et al.…”
mentioning
confidence: 99%
“…They are potential source of novel medically important natural products with diverse antimicrobial, anti-inflammatory, antiviral, antitumor, anti-malarial or immunosuppressive activities (Strobel et al, 2004; Nisa et al, 2015; Liu et al, 2016). Endophytic fungi are thus considered a promising reservoir of natural products with interesting medical bioactivities.…”
Section: Introductionmentioning
confidence: 99%